2020
DOI: 10.1002/aoc.6133
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4@L‐lysine‐Pd(0) organic–inorganic hybrid: As a novel heterogeneous magnetic nanocatalyst for chemo and homoselective [2 + 3] cycloaddition synthesis of 5‐substituted 1H‐tetrazoles

Abstract: An efficient and sustainable synthetic protocol has been presented to synthesis and 5-substituted 1H-tetrazole privileged heterocyclic substructures. The synthetic protocol involves two-component reaction between aryl nitriles and NaN 3 in water using complex of L-lysine-palladium nanoparticles (NPs) modified Fe 3 O 4 nanoparticles as magnetically separable, recyclable, and reusable heterogeneous catalyst. Magnetically retrievable L-lysine-Pd(0) modified Fe 3 O 4 nanoparticles were applied in [2 + 3] cycloaddi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The other group reported that Aryl nitrile was refluxed with sodium azide in water for 1 h at 100°C in the presence of Fe 3 O 4 @L‐lysine‐Pd(0) MNPs (0.30 mol%) as catalyst to yield 5‐substituted‐1H‐tetrazole 70%–99% (Scheme 9; Ashraf et al, 2021). This method offers various advantages, including fast recovery, reusability of Pd NPs, quick reaction time, and the use of water as a green solvent.…”
Section: Conventional Approachmentioning
confidence: 99%
“…The other group reported that Aryl nitrile was refluxed with sodium azide in water for 1 h at 100°C in the presence of Fe 3 O 4 @L‐lysine‐Pd(0) MNPs (0.30 mol%) as catalyst to yield 5‐substituted‐1H‐tetrazole 70%–99% (Scheme 9; Ashraf et al, 2021). This method offers various advantages, including fast recovery, reusability of Pd NPs, quick reaction time, and the use of water as a green solvent.…”
Section: Conventional Approachmentioning
confidence: 99%
“…Recent advances in this area were summarized in the well documented review by Rahul Shrivastava and co-workers 25 . For the synthesis of 5-substituted tetrazole via [3 + 2] cycloaddition reaction, two interesting reports by Tamoradi and co-workers, described the use of magnetic Fe 3 O 4 @tryptophan–La and Fe 3 O 4 @tryptopahn-Nd in water @ 80 °C 26 , 27 , Fe 3 O 4 -adenine-Zn was used in PEG 400 at 120 °C 28 Fe 3 O 4 @tryptophan@Ni was reported to work in PEG 400 at 120 °C and a palladium(0) based nano-catalyst, Fe 3 O 4 @ l -lysine-Pd(0), was described by Ashraf and co-workers to work in water at 100 °C 29 . For the synthesis of 1-substituted tetrazole derivatives via multicomponent reaction (MCR), Habibi and co-workers have reported the use of Fe 3 O 4 @5,10-dihydropyrido[2,3- b ]quinoxaline-7,8-diol copper and Fe 3 O 4 @1,10-phenanthroline-5,6-diol@Mn complexes in the reaction between amine, ethyl orthoformate and sodium azide under solvent-free conditions 30 , 31 A bifunctional magnetite nano-catalyst (Fe 3 O 4 /HT-NH 2 -Cu II ) was used by Salimi and Zamanpour group in the reaction between aromatic amines, ethyl orthoformate and sodium azide in water @ 90 °C 32 , and Salimi and co-workers also reported the use of Fe 3 O 4 @HT@AEPH 2 -Co II in the same MCR between amine, ethyl orthoformate and solidum azide in water at 90 °C 33 .…”
Section: Introductionmentioning
confidence: 99%